PEMBELAJARAN KONTEKSTUAL STRATEGI REACT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA - Aen Nurul Aen (Universitas Galuh, 2021)
ABSTRACTThe purpose of this study was to determine the application of contextual learning REACT strategy to improve student achievement in social studies subjects in class V SD Negeri Karangtengah, Kota Tasikmalaya. The method used in this research is Classroom Action Research. This rerearch procedures include determining the focus of the problem, planning actions, implementing actions, observation and interpretation, analysis and reflection. The instruments used in this study were the observation sheets and tests. The results of data analysis showed that in the first cycle the average student learning outcomes were 64.23 with learning completeness of 64.23% or as many as 16 students. In the application of cycle II the average student learning outcomes is 80.62 with student learning completeness of 88.46% or as many as 23 students. The increase in student learning outcomes is seen from the difference in the average value of the first cycle and the second cycle, namely 16.38, while the learning completeness increases by 26.92%. This means that contextual learning of the REACT strategy can be applied and can improve student social studies learning outcomes.Keywords: contextual learning, REACT strategy, student achievementABSTRAKPenelitian ini bertujuan mengetahui penerapan pembelajaran kontekstual strategi REACT untuk meningkatkan prestasi belajar siswa pada mata pelajaran IPS di kelas V SD Negeri Karangtengah Kota Tasikmalaya. Metode penelitian ini berupa Penelitian Tindakan Kelas (PTK). Prosedur PTK mencakup penetapan fokus permasalahan, perencanaan tindakan, pelaksanaan tindakan diikuti dengan observasi dan interpretasi, analisis dan refleksi. Instrumen yang digunakan dalam PTK ini adalah lembar observasi dan tes. Hasil analisis data menunjukkan siklus I rata-rata hasil belajar siswa adalah 64,23 dengan ketuntasan belajar sebesar 64,23% atau sebanyak 16 orang siswa, sedangkan pada penerapan siklus II rata-rata hasil belajar siswa adalah 80,62 dengan ketuntasan belajar siswa sebesar 88,46% atau sebanyak 23 orang siswa. Peningkatan hasil belajar siswa dilihat dari selisih nilai rata-rata siklus I dan siklus II yaitu 16,38 sedangkan pada ketuntasan belajar meningkat sebesar 26,92%. Hal ini dapat diartikan bahwa pembelajaran kontekstual strategi REACT mampu diterapkan dan dapat meningkatkan hasil belajar IPS siswa.Kata Kunci: Pembelajaran Kontekstual, Strategi REACT, Prestasi Belajar